Setting up regional diagnostic reference levels for pediatric interventional cardiology in Latin America and the Caribbean countries: preliminary results and identified challenges. (1st September 2022) - Ubeda, C; Vano, E; Perez, M D; Jímenez, P; Ramirez, R; Nader, A; Miranda, P; Azcurra, P; Damsky, J; Capdevila, S; Oliveira, M; Albuquerque, J; et al.
Abstract: The goal of the present study was to propose a set of preliminary regional diagnostic reference levels (DRLs) for pediatric interventional cardiology (IC) procedures in Latin America and the Caribbean countries, classified by age and weight groups. The study was conducted in the framework of the Optimization of Protection in Pediatric Interventional Radiology in Latin America and the Caribbean program coordinated by the World Health Organization and the Pan American Health Organization in cooperation with the International Atomic Energy Agency. The first step of the program was focused on pediatric IC. Dose data from diagnostic and therapeutic procedures were collected between December 2020 and December 2021. Regional DRLs were set as the third quartile of patient dose data (kerma area product) collected in 18 hospitals from 10 countries in an initial sample of 968 procedures. DRLs were set for four age bands and five weight ranges. The values obtained for the four age bands (<1 yr, 1 to <5 yr, 5 to <10 yr and 10 to <16 yr) were 2.9, 6.1, 8.8 and 14.4 Gy cm 2 for diagnostic procedures, and 4.0, 5.0, 10.0 and 38.1 Gy cm 2 for therapeutic procedures, respectively. The values obtained for the five weight bands (<5 kg, 5 to <15 kg, 15 to <30 kg, 30 to <50 kg and 50 to <80 kg) were 3.0, 4.5, 8.1, 9.2 and 26.8 Gy cm 2 for diagnostic procedures and 3.7, 4, 3, 7.3, 16.1 and 53.4 Gy cm 2 for therapeutic procedures, respectively. While initial data were collected manually as patient dose management systems (DMSs) were not available in most of the hospitals involved in the program, a centralized automatic DMS for the collection and management of patient dose indicators has now been introduced and is envisaged to increase the sample size. The possibility of alerting on high dose values and introducing corrective actions will help in optimization.